TAKISCIA (Tas Lukis Cinta Indonesia) : Pemanfaatan MMT Bekas, Kain Perca Sebagai Peluang Usaha - Fatmawati, Dewi; Meiliani, Apit; Ariyanto, Afif; Nafis, Nabil An; Lestari, Ninuk Endah Sri (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
Takiscia is a program of student creativity and entrepreneurial use of MMT former patchwork made as eco-friendly business opportunity selling high value Unnes student. Takiscia bag is patterned images or writing our love of the homeland. Buyers can also order bags with motifs desired, the purpose entrepreneurial creativity of students this program, of which the former is to make use of MMT and patchwork to be used as a bag painting paintings show our love towards Indonesia, foster creativity and entrepreneurship for students to create business opportunities profit-oriented. The method used, the production preparation, production implementation, production and marketing. This program has been implemented three months, from month to month of production is increasing. This program has been running from April to July. In April production was held on Saturday April 26, 2014 with the results of 20 pieces of bags. But in April the bag just sold 15 pieces. The second production was held on Wednesday, June 14, 2014 with the results of 50 pieces of bags. In June the team was able to sell 50 pieces of bags coupled with the remaining 5 pieces bag in April. The third production held on Friday July 4, 2014 with the results of 60 fruit bags. PKM team sales efforts Takiscia hope this can continue with ways to expand their market, and follows the activities of the exhibition held government and private institutions. So it can evolve as expected. Based on the description above, the benefits of this program is to encourage people to love the country Indonesia with two new ways to love domestic products and motifs that show our love towards Indonesia, increasing the innovative creativity of students in finding work that can be exploited as a business opportunity, and improve high sales value by utilizing the former MMT to be used as a purse painted with good quality and fashion style can be interesting. Keywords : useful mm second, business opportunities